1989
DOI: 10.1128/aem.55.1.43-49.1989
|View full text |Cite
|
Sign up to set email alerts
|

Acute Copper and Cupric Ion Toxicity in an Estuarine Microbial Community

Abstract: Copper was acutely toxic to the estuarine microbial community of Middle Marshes, N.C. Under ambient water quality conditions, 10 ,ug of added total copper [Cu(II)] liter-' reduced the CFU bacterial abundance by up to 60% and inhibited the amino acid turnover rate (AATR) by as much as 30%. Copper toxicity, however, was a quantitative function of free cupric ion (Cu2+) activity that was not directly related to Cu(II) or ligand-bound copper. By using a nitrilotriacetic acid-cupric ion buffer to control pCu (-log … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 37 publications
0
18
2
1
Order By: Relevance
“…However, thymidine incorporation in aerobic and anaerobic slurries of marine sediments was slightly more sensitive to organic aromatic pollutants than uptake of ['4C]glucose [8]. ['4C]Glucose turnover in pond water [20] and in river water [6] and amino acid turnover in estuarine waters [19] were as sensitive to the addition of 10 to 100 pg L-' copper as thymidine incorporation was in our study. Jonas et al [7] opined that thymidine incorporation should be a more universal parameter for testing acute toxicity of compounds than the activity specific to certain types of bacteria, e.g., sulfate reduction, because thymidine is so upiversally utilized by bacteria.…”
Section: Relative Sensitivity Of Microbial Parameterscontrasting
confidence: 50%
“…However, thymidine incorporation in aerobic and anaerobic slurries of marine sediments was slightly more sensitive to organic aromatic pollutants than uptake of ['4C]glucose [8]. ['4C]Glucose turnover in pond water [20] and in river water [6] and amino acid turnover in estuarine waters [19] were as sensitive to the addition of 10 to 100 pg L-' copper as thymidine incorporation was in our study. Jonas et al [7] opined that thymidine incorporation should be a more universal parameter for testing acute toxicity of compounds than the activity specific to certain types of bacteria, e.g., sulfate reduction, because thymidine is so upiversally utilized by bacteria.…”
Section: Relative Sensitivity Of Microbial Parameterscontrasting
confidence: 50%
“…This mechanism may extend to a protective role against toxicants for the host sponge. Jonas (1989) demonstrated that free Cu 21 and not total or ligand-bound copper was responsible for toxicity to an estuarine bacterial community. In our experiments, the density of total culturable bacteria was reduced significantly at and above 1.7 mg l 21 Cu 21 after 14 days (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…These observations agreed with those of Banoub (19841, who found that organic matter considerably reduced the toxicity of copper to bacterial populations in the Rivers Rhine and Neckar and in sewage sludge. Similarly, Zevenhuizen (1979) and Jonas (1989) showed that additions of complexing substances alleviated the free Cu-ion concentration to a tolerable level for the growth of surviving bacteria. In this study, it was hypothesized whether or not increased community tolerance had been induced in the moderately copper-exposed waters in the tests.…”
Section: Discussionmentioning
confidence: 94%